Structure Optimization and Numerical Simulation of Nozzle for High Pressure Water Jetting. (21st June 2015) - Zhang, Shuce; Tao, Xueheng; Lu, Jinshi; Wang, Xuejun; Zeng, Zhenhua
Abstract : Three kinds of nozzles normally used in industrial production are numerically simulated, and the structure of nozzle with the best jetting performance out of the three nozzles is optimized. The R 90 nozzle displays the most optimal jetting properties, including the smooth transition of the nozzle's inner surface. Simulation results of all sample nozzles in this study show that the helix nozzle ultimately displays the best jetting performance. Jetting velocity magnitude alongY andZ coordinates is not symmetrical for the helix nozzle. Compared to simply changing the jetting angle, revolving the jet issued from the helix nozzle creates a grinding wheel on the cleaning surface, which makes not only an impact effect but also a shearing action on the cleaning object. This particular shearing action improves the cleaning process overall and forms a wider, effective cleaning range, thus obtaining a broader jet width.